ANALISIS IMPLEMENTASI GERAKAN LITERASI SEKOLAH DI SD NEGERI 1 BLANG MANGAT, LHOKSEUMAWE - Muri Datul Jinan; Susi Yusrianti; Abdul Kadir (STKIP Subang, 2026)
The School Literacy Movement (Gerakan Literasi Sekolah/GLS) is a national program designed to foster students' literacy culture through reading habituation and literacy-based learning activities in schools. However, the implementation of GLS in elementary schools continues to face various challenges that affect its effectiveness. This study aimed to analyze the implementation of the School Literacy Movement at SD Negeri 1 Blang Mangat, Lhokseumawe City, using the Context, Input, Process, Product (CIPP) model. This study employed a qualitative approach with a descriptive-analytical research design. Data were collected through interviews, observations, and documentation, and were analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The findings revealed that the implementation of GLS has been carried out through a 15-minute reading activity before the learning process in all grade levels. However, the program has not been implemented optimally because the school has not established an official decree or technical guidelines to support GLS implementation, literacy facilities—particularly reading materials—remain limited, and teachers' understanding of the GLS stages is still focused mainly on the habituation stage. Nevertheless, the program has positively contributed to developing students' reading habits before classroom instruction. Therefore, strengthening school policies, improving the availability of reading materials, and enhancing teachers' competencies are essential to ensure a more effective and sustainable implementation of the School Literacy Movement.